Eksplorasi Peran Konten Marketing Dalam Meningkatkan Daya Tarik Wisatawan Flora Wisata Santerra de Laponte - Sari, Cindy Putri Sukma; Nurhajati, Nurhajati; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to explore the role of content marketing in enhancing the attractiveness of tourist destinations, focusing on the case of Flora Wisata Santerra de Laponte. The research is motivated by the increasing competition in the tourism industry and the necessity for managers to innovate in digital promotion strategies. Literature review suggests that content marketing is effective in building destination image and increasing tourist interest. This research employs a qualitative approach through in-depth interviews and observations involving both managers and visitors. The results indicate that content marketing strategies highlighting unique attractions, visitor experiences, and creative use of social media significantly boost visibility and tourist visits. However, challenges remain in aligning content with diverse visitor preferences and objectively measuring content effectiveness. In conclusion, relevant and adaptive content marketing can strengthen the appeal of tourist destinations, but continuous evaluation is required to maintain strategy effectiveness. This study offers practical and theoretical contributions for tourism managers in designing more market-responsive promotional strategies. Keywords: Content Marketing; Tourist Attraction; Digital Promotion Strategy; Visitor Experience; Social Media; Destination Innovation; Marketing Effectiveness.